Statistical and Economic Analysis of the Rhine-Main-Danube Canal, the Bridge between the North Sea and the Black Sea: Array - Chirosca, Ana Maria; Rusu, Liliana (Journal of Danubian Studies and Research, 2021)
The Rhine-Main-Danube Canal, known as the Europe Canal, is 171 km long and is the shortest navigable connection between the Black Sea and the North Sea since 1992, via the Rhine, Main, Danube-Black Sea Canal and Danube. Through the ensemble between the Rhine-Main-Danube Canal and the Danube-Black Sea Canal, a direct transport axis is created between the port of Rotterdam, the largest port in terms of freight transport, and the port of Constanta. The importance of a study on navigation on this channel is due to the economic growth and implicitly to the growth of goods and services. In this paper, a study on the economic impact of the Rhine-Main-Danube Canal was conducted due to the large flow of goods transited along it, as well as the diversification of goods transported. The main types of goods transported were identified. Also, the navigation conditions on the canal were studied and the most crowded and most dangerous areas were identified.